In Pursuit of Meaningful Use of Learning Goals in Residency: A Qualitative Study of Pediatric Residents. (June 2016) - Lockspeiser, Tai M.; Li, Su-Ting T.; Burke, Ann E.; Rosenberg, Adam A.; Dunbar, Alston E.; Gifford, Kimberly A.; Gorman, Gregory H.; Mahan, John D.; McKenna, Michael P.; Reed, Suzanne; Schwartz, Alan; Harris, Ilene; et al.
Abstract : Purpose: Medical education aims to equip physicians for lifelong learning, an objective supported by the conceptual framework of self-regulated learning (SRL). Learning goals have been used to develop SRL skills in learners across the medical education continuum. This study's purpose was to elicit residents' perspectives on learning goal use and to develop explanations suggesting how aspects of the learning environment may facilitate or hinder the meaningful use of learning goals in residency. Method: Resident focus groups and program director interviews were conducted in 2012–2013, audio-recorded, and transcribed. Programs were selected to maximize diversity of size, geographic location, type of program, and current use of learning goals. Data were analyzed using the constant comparative method associated with grounded theory. Further analysis compared themes frequently occurring together to strengthen the understanding of relationships between the themes. Through iterative discussions, investigators built a grounded theory. Results: Ninety-five third-year residents and 12 program directors at 12 pediatric residency programs participated. The analysis identified 21 subthemes grouped into 5 themes: program support, faculty roles, goal characteristics and purposes, resident attributes, and accountability and goal follow-through. Review of relationships between the themes revealed a pyramid of support with program support as the foundation that facilitates the layers above it, leading to goal follow-through. Conclusions: Program support facilitates each step of the SRL process that leads to meaningful use of learning goals in residency. A strong foundation of program support should include attention to aspects of the implicit curriculum as well as the explicit curriculum. Abstract : Supplemental Digital Content is available in the text.